Perforated diverticulitis of the appendix: ultrasonographic diagnosis - Lourenço,Rafael Burgomeister (2011)
ABSTRACT Appendiceal diverticulitis is an uncommon condition, mimicking appendicitis, but with greater risk of perforation and complications. Preoperative diagnosis is rare, but can be achieved by ultrasonography as identification of the diverticulum and classical signs of appendicitis. We report a case of ultrasonographic diagnosis of a perforated appendiceal diverticulitis in an adult male and discuss this condition.